Self‐perceived halitosis among young adults undergoing orthodontic treatment. - Banjar, Arwa A.; Hassan, Shaymaa M; Alyafi, Rusha A.; Alawady, Sara A.; Alghamdi, Morouj H.; Baik, Khadijah M. (International Journal of Dental Hygiene, 2022)
Introduction: Halitosis is a common oral health problem that significantly impacts the quality of life of the affected individuals. In most cases, poor oral hygiene is responsible for the problem. Orthodontic therapy aims to correct malocclusion using different devices. It has been suggested that orthodontic treatment can promote gingival health by facilitating daily oral hygiene measures. However, the treatment may harm gingival health as these appliances may lead to a more significant accumulation of plaque, increasing the microbial load in the subgingival environment leading to halitosis. Objective: The primary goal of this survey is to assess the prevalence of self‐perceived halitosis in patients undergoing orthodontic treatment. Materials and Methods: An online questionnaire was randomly distributed to patients undergoing orthodontic treatment. A total of 289 subjects completed the questionnaire. It included questions about: demographic data, medical history, social habits, past dental treatment and oral hygiene habits. Descriptive statistics as frequency distributions and percentages were calculated for the study variables. Results: The prevalence of self‐perceived halitosis was 41.5%. The majority of the participants started to notice this problem during and after orthodontic treatment (62.5%). A statistically significant correlation was found between the regular dental visits and halitosis in patients with fixed orthodontic appliances (p‐value = 0.010). Also, those patients had a substantial increase in tongue coating formation (p‐ value = 0.010). Conclusion: Self‐perceived halitosis is a common problem in patients receiving orthodontic treatment.